2021
DOI: 10.1097/mao.0000000000003383
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Lower Cranial Nerve Function Between Tympanojugular Paraganglioma Class C1/C2 With and Without Intracranial Extension: A Four-Decade Experience

Abstract: Objective: To compare preoperative and postoperative lower cranial nerve (LCN) function between Class C1 and C2 tympanojugular paraganglioma (TJP) with/without intracranial intradural (Di)/extradural (De) extensions, according to the experience of a single surgeon over four decades. Study Design: Retrospective review. Setting: Quaternary referral center for otology and skull base surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
(146 reference statements)
0
2
0
Order By: Relevance
“…Prasad et al noticed that the presence of intradural extension is usually associated with infiltration of the LCNs 3 . Grinblat et al reported that early and limited C1 and C2 tumors without medial wall invasion reduces the risk of dysfunctionality of LCNs 29 . Thus resection of early JPs (classes C1-C2), where the lateral aspect of the jugular bulb is involved and the medial wall is not infiltrated, makes preservation of the LCNs possible.…”
Section: Discussionmentioning
confidence: 99%
“…Prasad et al noticed that the presence of intradural extension is usually associated with infiltration of the LCNs 3 . Grinblat et al reported that early and limited C1 and C2 tumors without medial wall invasion reduces the risk of dysfunctionality of LCNs 29 . Thus resection of early JPs (classes C1-C2), where the lateral aspect of the jugular bulb is involved and the medial wall is not infiltrated, makes preservation of the LCNs possible.…”
Section: Discussionmentioning
confidence: 99%
“…For Fisch C1 and C2, with or without Di or De extensions, complete removal of the tumor is possible, preventing functional deficits for lower cranial nerves, with less than 10% of new postoperative nerve palsies in cases with Di/De, and none in those without extensions [ 74 ].…”
Section: Treatment Optionsmentioning
confidence: 99%